Outbreak of hepatitis E virus infection in Darfur, Sudan: effectiveness of real-time reverse transcription-PCR analysis of dried blood spots. - Mérens, A; Guérin, P; Guthmann, J; Nicand, E (2009)
Biological samples collected in refugee camps during an outbreak of hepatitis E were used to compare the accuracy of hepatitis E virus RNA amplification by real-time reverse transcription-PCR (RT-PCR) for sera and dried blood spots (concordance of 90.6%). Biological profiles (RT-PCR and serology) of asymptomatic individuals were also analyzed.